Revitalizing Personal Resources: A study on organizational stress management through the implementation of yoga in the workplace - O'Fee, Kerrith (The IIE, 2020)
Stress is an inescapable component of our daily lives and presents significant risks to people in both their personal and professional lives. Within the context of work, negative stress can significantly harm organizational outcomes making it imperative for companies to effective assist employees in stress management. This study aimed to assess whether the implementation of yoga, as a stress management intervention, would lead to a significant decrease in perceived stress amongst employees. Based on prior research indicating an association between yoga and stress levels in various international contexts, it was hypothesised that results would display a reduction in perceived stress with the implementation of the yoga intervention. Data was collected through the use of the Perceived Stress Scale Survey by Cohen as it is a reliable scientific measure (Cronbach’s alpha = 0.78) providing quantitative values of perceived stress, and data was analyzed using both a dependent and independent samples t-test for analysis. Findings of the study were inconclusive as although yoga was found to significantly reduce stress within the yoga group (t = 4.04, p = 0.0004), the overall decrease in comparison to the control group produced a non-statistically significant difference(t = 0.96, p = 0.35).
Keywords: Organizational stress; Workplace stress; Personal resources; Yoga; Stress management